2019
DOI: 10.3329/bmj.v46i2.40218
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Verapamil Adjuvant with Local Anaesthetic Mixtures in Supraclavicular Brachial Plexus Block

Abstract: Among the various approaches to block brachial plexus , supraclavicular approach offers a high success rate for elbow, forearm and hand surgery . Various adjuvant drugs have been used with local anesthetics in order to decrease the time of onset and prolong the duration and quality of regional blocks. So efforts were made to combine the adjuvant with local anesthetics to improve patient and surgeon satisfaction. In this randomized study we tried to see the effect of verapamil in brachial plexus block as an adj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Dr. Md. Arman Ali, et al [12] found similar results in a similar study and concluded that verapamil can be used as an adjuvant to decrease the onset time of sensory and motor blocks of bupivacaine in supraclavicular block. Sidharth sraban routray, et al [11] in their study also concluded that Verapamil, when added to Levobupivacaine in supraclavicular brachial plexus, increased the duration of sensory and motor block.…”
Section: Discussionmentioning
confidence: 63%
“…Dr. Md. Arman Ali, et al [12] found similar results in a similar study and concluded that verapamil can be used as an adjuvant to decrease the onset time of sensory and motor blocks of bupivacaine in supraclavicular block. Sidharth sraban routray, et al [11] in their study also concluded that Verapamil, when added to Levobupivacaine in supraclavicular brachial plexus, increased the duration of sensory and motor block.…”
Section: Discussionmentioning
confidence: 63%
“…In addition, a person who participates in voluntourism is driven by motivation. Several studies (Ali & Rahman, 2019;Han et al, 2019;Otoo & Amuquandoh, 2014;Proyrungroj, 2017) additionally propose that the inspiration of volunteer sightseers is multi-layered, and their inspiration incorporates both to and fro factors. In the meantime, persuasive variables are the hypothetical methodologies most broadly utilized to grasp traveler inspiration (John & Larke, 2016;Michael et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Local anaesthetic agent provides analgesia not more than 4-8 hours [1] . Drugs belonging to calcium blockers, opioids, ketamine, adrenaline, alpha2 adrenergic agonist are used as adjuvants to increase analgesic ability and decrease the incidence of side effects [2] . Supraclavicular brachial plexus block is carried out at the division level, which had rapid onset and deep level of block.…”
Section: Introductionmentioning
confidence: 99%
“…Supraclavicular brachial plexus block is carried out at the division level, which had rapid onset and deep level of block. In recent time, supraclavicular block has gained extensive fame with addition of adjuncts to local anaesthetic solution to increase its efficacy and duration [2,3] . Verapamil is a drug of calcium channel blocker that is used as adjuvant to local anaesthetic agents in peripheral nerve block.…”
Section: Introductionmentioning
confidence: 99%